Red Blood Cell Alloimmunization in Sickle Cell Disease: Advantage of Ethnic Heritage between Donors and Patients in Jeddah, Saudi Arabia. (28th October 2021) - Anwar, F; Almohammadi, M; Garni, A; Jamallail, S; Alsamkari, W; Alsafi, A
Abstract: Introduction/Objective: Red blood cell (RBC) transfusion is frequently required for patients with sickle cell disease (SCD). Development of alloantibodies in these patients complicates the blood bank process needed to identify these antibodies and to find compatible RBC units. The rate of alloimmunization has been reported as high as 47% in one study and 34.2% in another study from Eastern region of Saudi Arabia. The purpose of this study was to determine incidence and rate of RBC alloimmunization in the Saudi population in the Western region in SCD. Methods/Case Report: A retrospective analysis of the immunohematological and transfusion history of a total of 161 SCD patients was reviewed, of which there 95 males and 66 females. All patients had erythrocytapheresis, ranging from one to 24 full red cell exchange sessions. A total of 490 red cell exchanges were performed and 4, 914 units of blood were used. Extended compatibility to RhCcEe and K antigen was performed. Patient who developed alloimmunization to any of RhCcEe and K antigen were matched for Kidd, Duffy and MSN antigens for subsequent RBC requirements. Results (if a Case Study enter NA): The RBC alloimmunization incidence was 18% with a rate of 0.6 antibodies per 100 RBC transfusions. Alloimmunization in females was significantly higher than in the patients. Eighteen (11.2%) female patients demonstrated antibodies as compared to eleven (6.8%) male patients. Twelve patients (7.4%) had a history of at least one alloantibody and 17 (10.6%) had more than one. Antibodies found were directed against E (7.4%), K (5.6%), and D, C, c, S, M, Lea, Jk a, Chido/Rodgers, Fy a. Seven (4.3%) patients also had warm autoantibodies. Conclusion: RBC alloimmunization incidence and rate in our study was lower to those reported in less heterogeneous population of donors and patients. Nonetheless, RBC alloimmunization still occurs in patients with SCD, often due to Rh variants or lack of consistency in the application of prophylactic antigen matching between institutions. Therefore, we believe that this rate can still be further reduced if all centers in the region establish transfusion programs to include at least RhCcEe and K phenotypic compatibility and communication mechanisms between major treating centers and transfusion centers in smaller cities to minimize the risks of exposing the patient to different RhCcEe and K phenotype and of developing RBC alloimmunization.